PRESENTATION INFORMATION PRODUCTS HOUSEHOLD TOOL WITH MICROSOFT VISUAL BASIC IN. ELECTROLUX INDONESIA - Purwo Hadi Santoso; Ire Puspa Wardhani, SKom, MMSI Ire Puspa Wardhani, SKom, MMSI (Jurnal Sistem Informasi, 2003)
Marketing system on the branches of PT. Electroulux Indonesia still use manual way,through the brochures. Because it takes many pieces of brochures for various types ofgoods. This causes various problems, such as the limited number of brochures areavailable as well as new product information could not immediately known, becausethe brochures of the products concerned are not yet available.By using Microsoft Visual Basic author makes the presentation of informationproducts Page. Electrolux Indonesia, which is expected to assist in explaining thetasks of selling a product information to prospective customers. Presentation of theinformation displayed in the form of product data and pictures, plus a search modulethat allows you to search for a product the goods in question.